Positional and angular tracking of HDR 192Ir source for brachytherapy quality assurance using radiochromic film dosimetry. Issue 12 (2nd November 2020) - Aldelaijan, Saad; Devic, Slobodan; Bekerat, Hamed; Papaconstadopoulos, Pavlos; Schneider, James; Seuntjens, Jan; Cormack, Robert A.; Buzurovic, Ivan M.
Abstract : Purpose: To quantify and verify the dosimetric impact of high‐dose rate (HDR) source positional uncertainty in brachytherapy, and to introduce a model for three‐dimensional (3D) position tracking of the HDR source based on a two‐dimensional (2D) measurement. This model has been utilized for the development of a comprehensive source quality assurance (QA) method using radiochromic film (RCF) dosimetry including assessment of different digitization uncertainties. Methods: An algorithm was developed and verified to generate 2D dose maps of the mHDR‐V2 192 Ir source (Elekta, Veenendaal, Netherlands) based on the AAPM TG‐43 formalism. The limits of the dosimetric error associated with source (0.9 mm diameter) positional uncertainty were evaluated and experimentally verified with EBT3 film measurements for 6F (2.0 mm diameter) and 4F (1.3 mm diameter) size catheters at the surface (4F, 6F) and 10 mm further (4F only). To quantify this uncertainty, a source tracking model was developed to incorporate the unique geometric features of all isodose lines (IDLs) within any given 2D dose map away from the source. The tracking model normalized the dose map to its maximum, then quantified the IDLs using blob analysis based on features such as area, perimeter, weighted centroid, elliptic orientation, and circularity. The Pearson correlation coefficients (PCCs) between these features and source coordinates ( x, y, z, θy, θz ) were calculated. To experimentally verify the accuracy of the tracking model, EBT3 film pieces were positioned within a Solid Water® (SW) phantom above and below the source and they were exposed simultaneously. Results: The maximum measured dosimetric variations on the 6F and 4F catheter surfaces were 39.8% and 36.1%, respectively. At 10 mm further, the variation reduced to 2.6% for the 4F catheter which is in agreement with the calculations. The source center ( x, y ) was strongly correlated with the low IDL‐weighted centroid (PCC = 0.99), while the distance to source ( z ) was correlated with the IDL areas (PCC = 0.96) and perimeters (PCC = 0.99). The source orientation θy was correlated with the difference between high and low IDL‐weighted centroids (PCC = 0.98), while θz was correlated with the elliptic orientation of the 60–90% IDLs (PCC = 0.97) for a maximum distance of z = 5 mm. Beyond 5 mm, IDL circularity was significant, therefore limiting the determination of θz (PCC ≤ 0.48). The measured positional errors from the film sets above and below the source indicated a source position at the bottom of the catheter (−0.24 ± 0.07 mm). Conclusions: Isodose line features of a 2D dose map away from the HDR source can reveal its spatial coordinates. RCF was shown to be a suitable dosimeter for source tracking and dosimetry. This technique offers a novel source QA method and has the potential to be used for QA of commercial and customized applicators.